Physical education and health : Volume II - Aparato, Conrado R.; Talaroc-Brebante, Zyra Ruth; Dajime, Peter Fermin; Fernando-Callo, Lualhati (84-86 P. Florentino st., Sta. Mesa Heights, Quezon City : Rex Book Store Inc., 2016)
physical education a health volume II aims to guide senior high school students in finding physical activities that they can maintain for the rest of their lives. it equips students with 21st century skills that enhance them as independent learners as well as leaders in their community. This worktext reviews students knowldege on various recreational activities and encourages them to practice these activities to increase the likelihood of successful participation. Moreover, these recreational activities should be viewed as vehicles of learning important life skills such as communication, collaboration, time management, and environment protection.
Brief history and nature of dance -- Elements of dance -- Dance appreciation and composition -- Dance as an art -- Dance as a competition -- Dance-related injuries -- Nature and background of outdoor recreation -- Aquatic Activities -- Mountaineering activities -- Safety practices in outdoor recreation -- Risk management of outdoor activities -- Budget and logistical issues
Includes bibliographical references and index
English